2000
DOI: 10.1016/s1097-2765(00)80414-1
|View full text |Cite
|
Sign up to set email alerts
|

VASA Mediates Translation through Interaction with a Drosophila yIF2 Homolog

Abstract: The Drosophila gene vasa (vas) encodes an RNA-binding protein required for embryonic patterning and germ cell specification. In vas mutants, translation of several germline mRNAs is reduced. Here we show that VAS interacts directly with the Drosophila homolog of yeast translation initiation factor 2, encoded by a novel gene, dIF2. Embryos produced by vas/+; dIF2/+ females have pattern defects and fewer germline progenitor cells, indicating a functional interaction between endogenous vas and dIF2 activities. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
116
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 39 publications
4
116
0
Order By: Relevance
“…mRNAs (Carrera et al 2000;Johnstone and Lasko 2004). This study suggests that Vas can itself discriminate among potential mRNA targets, although we cannot exclude that Vas may be recruited to other target mRNAs through indirect associations involving partner RNAbinding proteins.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…mRNAs (Carrera et al 2000;Johnstone and Lasko 2004). This study suggests that Vas can itself discriminate among potential mRNA targets, although we cannot exclude that Vas may be recruited to other target mRNAs through indirect associations involving partner RNAbinding proteins.…”
Section: Discussionmentioning
confidence: 81%
“…A DNA damage checkpoint that functions in the oocyte during meiotic prophase, after the 16-cell cyst has formed, regulates Vas activity (Ghabrial and Schü pbach 1999;Abdu et al 2002;Findley et al 2003;Theurkauf et al 2006;Chen et al 2007;Pane et al 2007). Vas binds to eIF5B, an essential translation initiation factor that functions in ribosomal subunit joining (Carrera et al 2000;Pestova et al 2000). In vasnull oocytes, grk translation is greatly reduced (Styhler et al 1998;Tomancak et al 1998), an effect also observed in oocytes that express only a form of Vas (Vas4617) that is specifically compromised for eIF5B binding (Johnstone and Lasko 2004).…”
mentioning
confidence: 99%
“…In Drosophila, Vasa stimulation by Tejas and/or Tapas in the nuage might be involved in the piRNA pathway (see below), whereas Vasa stimulation by Oskar in the pole plasm likely has a distinct role. Vasa was suggested to activate translation of mRNAs in the egg chamber through recruitment of eIF5B (Carrera et al 2000;Johnstone and Lasko 2004), which catalyzes ribosomal subunit joining to form elongation-competent ribosomes (Pestova et al 2000). Vasa has been shown to physically interact with eIF5B in yeast two-hybrid assays and pull-down experiments from lysates (Johnstone and Lasko 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the localization of VAS does not rely on its ability to bind RNA via the DEAD box RNA helicase, germ cell formation does [19]. More recent work revealed that VAS binds the translation initiation factor eIF5B [20]. A mutated form of VAS-GFP whose eIF5B binding activity has been greatly reduced has been used to study the functional significance of the VAS-eIF5B interaction [21].…”
Section: Germ Plasmmentioning
confidence: 99%
“…While these genes can sometimes be identified through phenotype-based screens that focus on the germline or by creating germline mutant clones [25], if a mutation blocks oogenesis at an early stage or is cell-lethal then any later function in oocyte patterning will not be uncovered. Biochemical approaches and direct protein interaction screens, such as the two-hybrid screen which identified a role for eIF5B in germ cell formation, will allow identification of somatic genes required for germ cell formation [20,26,27].…”
Section: Germ Plasmmentioning
confidence: 99%